Efektivitas Celengan untuk Melatih Pembiasaan Menabung bagi Siswa Down Syndrome - Iza Nurjanah; Jon Efendi (Jurnal Penelitian Pendidikan Khusus, 2018)
This study aims to determine the effectiveness of the medium piggy bank in getting used to saving children with Down syndrome grade IV in the SLB Kasih Ummi Padang. This study included aexperiment single subject research (SSR)with ABA design and data analysis techniques using graphical visual analysis. Subjects in this study were children with Down syndrome. Thetarget behavioral in this study is that children are accustomed to saving on their own consciousness. Data measured by the frequency in the analysis included the number of observationsconditions baseline  as much as four weeks, the condition of intervention as much as four weeks andconditions baseline both for five minggu.Hasil this study indicate that the media piggy bank saving refraction effective in training students with Down syndrome child is evident from the results of analysis on thecondition baseline secondthat children save every day for three consecutive weeks previously in thecondition of the baseline child does not save at all and in conditions of intervention the child saves every day for four consecutive weeks.